Use of Sealed Agar Plates for Bacterial Cultures Under Jungle Conditions - Moellering, Robert C. (1969)
Commercially available sealed blood-agar plates have been demonstrated to retain their usefulness for as long as 3 months under jungle conditions without refrigeration.